Pelatihan Penggunaan Google Form Pada Posyandu Perumahan Harapan Baru 2 Bekasi - Alexander, Allan D; Salkiawati, Ratna (Lembaga Penelitian, Pengabdian kepada Masyarakat dan Publikasi Universitas Bhayangkara Jakarta Raya, 2022)
Children are the next generation of the nation that will replace the previous generation, for that their development must be carefully considered, especially during the golden period of their life where this period is in the first 1000 days of their life which has an impact on children's physical and cognitive development. Posyandu is a health effort that is managed independently by the community in order to provide health services for mothers, babies and toddlers. The COVID-19 pandemic has brought posyandu activities to a halt, including the posyandu in the Perumahan Harapan Baru 2, Bekasi City. Google Form as an alternative to posyandu cards with the intention that posyandu activities, especially monitoring the growth of toddlers, can be carried out from house to house without having to create a crowd and still pay attention to health protocols, and in order to use them training needs to be made.